Social Arithmetic Learning Design Using the Sociodrama Method with the PMRI Approach - Mangelep, Navel O.; Pongoh, Frisca M.; Sulistyaningsih, Murni; Mandolang, Eunike; Mahniar, Ade (MARISEKOLA: Jurnal Matematika Riset Edukasi dan Kolaborasi, 2024)
Numeracy skills are essential for students today. However, there are still many students who still need to improve their numeracy abilities. Topics such as social mathematics require high numeracy skills. This research aims to produce a local instructional theory on social arithmetic material using the sociodrama method with the PMRI approach. This research was conducted at SMP Negeri 2 Tondano, with research subjects in classes XI MIA 1 (Pilot Experiment Class) and XI MIA 2 (Teaching Experiment Class). The research method used is the design research method, which includes preliminary design, teaching experiment, and retrospective analysis. This research collected data through video recordings, documentation, field notes, and observations. Meanwhile, the data was analyzed using qualitative analysis. The research results show that the resulting LIT is valid, practical, and effective for students studying social arithmetic topics. On the other hand, there is an increase in formal mathematics abilities, as demonstrated by students' conceptual understanding of how to apply their knowledge and experience when solving problems at the situational, referential, and general levels. Therefore, using the sociodrama method with the PMRI approach, the social arithmetic learning design is instrumental in increasing students' understanding and motivation in learning mathematics on social arithmetic material.